A rare case of massive hemoptysis: Long-term complication of thoracotomy; rib fracture - Guzey, Emine; Yalcinsoy, Murat; Reha Celik, Muhammed; Kutlu, Ramazan; Akel, Unal (Annals of Medical Research, 2021)
None
Keywords: Massive hemoptysis; thoracotomy; rib fracture